Media Pembelajaran Komputer Grafik Pada SMK Asa Telagawaru Berbasis Multimedia - Alpi Sahrin; Yuliadi Idrus; Mustakim (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2020)
Currently, education in the process has made use of learning media in the teaching and learning process. SMK ASA Telagawaru Central Lombok in its learning activities is still conventional. The learning model is only in the form of learning which is sufficiently displayed by means of a computer and LCD projector in presenting material, especially practicum subject matter, namely computer graphics. There is no use of multimedia-based learning media so that students are less interactive and learning is still centered on the teacher. With these problems, the authors developed a learning media with the waterfall method and Adobe Flash Professional CS6 tools. Learning media that are made interactive are suitable for use, easy for learners to learn and can be used for individual learning and learning contains computer graphics.